Fencing amplifies individual differences in movement with implications on survival for two migratory ungulates. Issue 3 (12th January 2023) - Xu, Wenjing; Gigliotti, Laura C.; Royauté, Raphaël; Sawyer, Hall; Middleton, Arthur D.
Abstract: Fences have recently been recognized as one of the most prominent linear infrastructures on earth. As animals traverse fenced landscapes, they adjust movement behaviours to optimize resource access while minimizing energetic costs of coping with fences. Examining individual responses is key for connecting localized fence effects with population dynamics. We investigated the multi‐scale effects of fencing on animal movements, space use and survival of 61 pronghorn and 96 mule deer on a gradient of fence density in Wyoming, USA. Taking advantage of the recently developed Barrier Behaviour Analysis, we classified individual movement responses upon encountering fences (i.e. barrier behaviours). We adopted the reaction norm framework to jointly quantify individual plasticity and behavioural types of barrier behaviours, as well as behaviour syndromes between barrier behaviours and animal space use. We also assessed whether barrier behaviours affect individual survival. Our results highlighted a high‐level individual plasticity encompassing differences in the degree and direction of barrier behaviours for both pronghorn and mule deer. Additionally, these individual differences were greater at higher fence densities. For mule deer, fence density determined the correlation between barrier behaviours and space use and was negatively associated with individual survival. However, these relationships were not statistically significant for pronghorn. By integrating approaches from movement ecology and behavioural ecology with the emerging field of fence ecology, this study provides new evidence that an extraordinarily widespread linear infrastructure uniquely impacts animals at the individual level. Managing landscape for lower fence densities may help prevent irreversible behavioural shifts for wide‐ranging animals in fenced landscapes. Abstract : By integrating approaches from movement ecology and behavioural ecology with the emerging field of fence ecology, this study provides new evidence that an extraordinarily widespread linear infrastructure, fencing, uniquely impacts animals at the individual level. Importantly, high fence density can amplify behavioural differences among individuals.